2023
DOI: 10.32604/csse.2023.021332
|View full text |Cite
|
Sign up to set email alerts
|

Design of Online Vitals Monitor by Integrating Big Data and IoT

Abstract: In this work, we design a multisensory IoT-based online vitals monitor (hereinafter referred to as the VITALS) to sense four bedside physiological parameters including pulse (heart) rate, body temperature, blood pressure, and peripheral oxygen saturation. Then, the proposed system constantly transfers these signals to the analytics system which aids in enhancing diagnostics at an earlier stage as well as monitoring after recovery. The core hardware of the VITALS includes commercial off-the-shelf sensing device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…21(a) -(j) illustrates the heart rate and body temperatures of ten volunteers which consists of data obtained from the healthcare monitoring system using the reference antenna and the proposed active antennas, without and with a PIN diode. From the figures, it can be observed that the heart rate of the volunteers ranges from 72 to 96 BPM which shows that despite variations in heart rate, all the recorded values remain within the normal range for an adult, which is between 60 and 100 BPM [61]. Moreover, the collection of body temperature data is carried out to assess the patient's body temperature condition.…”
Section: B Performance Evaluation Of the Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…21(a) -(j) illustrates the heart rate and body temperatures of ten volunteers which consists of data obtained from the healthcare monitoring system using the reference antenna and the proposed active antennas, without and with a PIN diode. From the figures, it can be observed that the heart rate of the volunteers ranges from 72 to 96 BPM which shows that despite variations in heart rate, all the recorded values remain within the normal range for an adult, which is between 60 and 100 BPM [61]. Moreover, the collection of body temperature data is carried out to assess the patient's body temperature condition.…”
Section: B Performance Evaluation Of the Systemmentioning
confidence: 99%
“…A rise in body temperature correlates with an increase in heart rate, while a decrease in body temperature corresponds to a decrease in heart rate. The temperature ranges from 30.20 to 37.80 °C, indicating a healthy range for an adult which is between 35 and 38 °C [61]. However, it is worth noting that some values might fall below or slightly above this range, which could be due to factors like individual variability, recent activities, or environmental conditions.…”
Section: B Performance Evaluation Of the Systemmentioning
confidence: 99%
“…In the works presented in [ 29 , 30 , 31 , 32 , 33 ], the continuous monitoring of vital signs such as breathing and heartbeat temperatures is carried out; these variables play an essential role in predicting diseases. The results highlight the significance of assessing these devices for telemonitoring and clinical decision making, illustrating the potential of wearable technology in real-time health monitoring.…”
Section: Related Workmentioning
confidence: 99%